AB0810 The 15% rule in scleroderma: The frequency of organ complications in systemic sclerosis (SSC). A systematic review. (23rd January 2014) - Muangchan, C.; Baron, M.; Pope, J.E.
Abstract : Background: The prevalence of each organ complication in scleroderma (SSc) varies by definition used. However, it is important to be aware of several complications that can be detected and treated. A simple rule of prevalence of organ complications in SSc can be helpful for clinicians. Objectives: This study was done to determine the frequency of several SSc features including organ involvement (lung, heart, digital ulcers DU, scleroderma renal crisis SRC, pulmonary arterial hypertensions PAH). Methods: A comprehensive literature search of the Medline-OVID/EMBASE, Pub Med, and Scopus databases from 1980 to November 30th, 2011 was conducted to identify relevant articles with at least 50 SSc patients. Search words were within organ systmes such as lung, heart, pulmonary artery, kidney, digital ulcers, arthritis, myopathy and secondary Sjogren's. Study quality was assessed using the STROBE checklist. Prevalence of each organ complication was extracted from studies. Pooled prevalence and odds ratios (ORs) were calculated using the random effects method, and between-study heterogeneity was quantified using the I-squared statistic. Results: 5916 articles were identified (913 from Embase, 1009 from PubMed and 3994 from Scopus). 5665 were excluded of which 4912 were irrelevant, 237 did not report organ prevalence, 183 were case reports, 193 were reviews, 111 had less than 50 patients, 24 were not in Egnlish and 5 were not obtained; leaving 251 articles for full text review with 80 included in the meta-analysis. Where available, frequencies were also included from the Canadian Scleroderma Reserach Group (a database with more than 1000 SSc patients). There were no GI complications at a prevalence of 15% (GERD and dysphagia are far higher) and RP is nearly 100%. Xray ILD was common but significant restrictive ILD on PFTs occurred in approximately 15%. Conclusions: Many complications in SSc occur 15% of the time including low FVC, PAH, diastolic dysfunction, clincal and echo cardiac changes, arrhythmias, inflammatory arthritis, myopathy, Sjogren's and digital ulcers. 15% of digital ulcers have complications. SRC is uncommon but occurs in almost 15% of dcSSc. This is a helpful rule for frequency of organ involvement in SSc. Disclosure of Interest: C. Muangchan: None Declared, M. Baron: None Declared, J. Pope Grant/Research support from: Funding for the CSRG is from the Canadian Institutes of Health Research (CIHR) and the Fonds de Recherché en Santé du Québec, as well as Scleroderma Society of Canada, Scleroderma Society of Ontario, Sclérodermie Québec and Cure Scleroderma Foundation